Chemical stability of sulfonated poly(benzimidazole)s in proton exchange membrane fuel cells: A comprehensive Ab initio mechanistical study. (March 2020) - Molavian, Mohammad Reza; Abdolmaleki, Amir; Firouz Tadavani, Koorosh; Eskandari, Kiamars
Abstract: Electrochemical reactions in fuel cells produce various radical species which lead to degradation of membranes. Desulfonation of membranes is the most important factor in reducing cell performance in the long term. The present study theoretically investigated the chemical stability of sulfonated poly(benzimidazole)s. Possible degradation mechanisms for two sulfonated poly(benzimidazole)s with different sulfonating agents (sPBI1 and sPBI2) was studied to provide valuable data. For sPBI1, H radical is the main destructive agent and desulfonation occurs by the addition of H radical to the imidazole ring and hemolytic CS cleavage. While the desulfonation of the imidazole ring in the presence of OH radical is unfavorable in sPBI1, in the sPBI2, both H and OH radicals play important roles through different mechanisms. Desulfonation by H radical occurs by addition to the imidazole ring and CN bond cleavage, but desulfonation by OH radical proceeds from an elimination reaction and CC formation. The results for model compounds were in agreement with experimental data from Fenton's test. Also, backbone degradation for both sPBI1 and sPBI2 were thermodynamically unfavorable, exhibits good chemical stability in the presence of active radicals.